2005
DOI: 10.1179/174328105x15913
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cooling in continuous casting and Leidenfrost temperature effects

Abstract: The present study was motivated by problems at continuous casting plants where a variety of thermally induced defects were observed. The paper outlines an experimental method for the measurement of cooling intensity in the secondary cooling area where nozzles are applied. The precision of a variety of experimental methods is discussed. The nozzles have been investigated in terms of pressure setting, the influence of casting speed, and behaviour in the overlapping areas. The tests have provided information on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 4 publications
0
31
0
1
Order By: Relevance
“…For the calculation of h s , it has been assumed that the slab surface temperature is always above Leidenfrost temperature 54) in the spray zone. At high temperature, the cooling water forms a stable film on the slab surface which protects the surface from the direct contact with the coolant.…”
Section: 75mentioning
confidence: 99%
“…For the calculation of h s , it has been assumed that the slab surface temperature is always above Leidenfrost temperature 54) in the spray zone. At high temperature, the cooling water forms a stable film on the slab surface which protects the surface from the direct contact with the coolant.…”
Section: 75mentioning
confidence: 99%
“…Bendig et al [14] indicated that the parameter that controlled heat transfer intensity above Leidenfrost temperature, i.e., within the film boiling regime, was the kinetic energy of drops, which is influenced by p a . In another work, Raudensky and Horsky [15] also reported that the heat transfer is influenced not only by w but that d and v also played significant roles. Even, it was indicated that the heat transfer coefficient was affected by the casting velocity, arguing an effect of the motion of the hot surface on the flow of liquid on it and on the formation of vapor in front and behind the impinging jet; however, no direct evidence of such claims was provided.…”
mentioning
confidence: 95%
“…Since it is not possible to determine the intensity of the air-water jets on an actual caster, it is necessary to transfer the investigation -of each jet individually -to the experimental laboratory device (Figure 4), which is capable of simulating the surface of a concast slab [8][9][10][11]. This device also allows the measurement of temperatures beneath the surface within the slab.…”
Section: Measuring Of Cooling Effect Of Nozzlesmentioning
confidence: 99%